2016
DOI: 10.1177/2047487316668150
|View full text |Cite
|
Sign up to set email alerts
|

High intensity exercise training in heart failure: Understanding the exercise “overdose”

Abstract: Editorial on article entitled: 'Effects of high intensity interval training on central hemodynamics and skeletal muscle oxygenation during exercise in patients with chronic heart failure' by Spee et al. 1 Exercise limitation is a well-established cardinal manifestation of the heart failure (HF) syndrome and its quantification through gas exchange analysis with objective measure of oxygen uptake (VO 2 ) provides the clinician with relevant information on pathophysiology and outcome.2,3 Exercise training is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…13 These findings were confirmed by a recent study which also showed that a HIIT benefit in submaximal exercise capacity was due to a peripheral rather than a central contribution. 14,15 Thus, raised expectations were lowered and the idea of an 'optimum' exercise programme for heart failure patients started to fade away, moving towards the concept of tailoring an exercise programme according to patient specificity. 16,17 The European Association of Preventive Cardiology Exercise Prescription in Everyday Practice and Rehabilitative Training (EXPERT) tool has been recently introduced, representing a digital training and decision support system, using algorithms including a number of variables, to enable an optimized exercise prescription for each individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 These findings were confirmed by a recent study which also showed that a HIIT benefit in submaximal exercise capacity was due to a peripheral rather than a central contribution. 14,15 Thus, raised expectations were lowered and the idea of an 'optimum' exercise programme for heart failure patients started to fade away, moving towards the concept of tailoring an exercise programme according to patient specificity. 16,17 The European Association of Preventive Cardiology Exercise Prescription in Everyday Practice and Rehabilitative Training (EXPERT) tool has been recently introduced, representing a digital training and decision support system, using algorithms including a number of variables, to enable an optimized exercise prescription for each individual.…”
Section: Introductionmentioning
confidence: 99%
“…13 These findings were confirmed by a recent study which also showed that a HIIT benefit in submaximal exercise capacity was due to a peripheral rather than a central contribution. 14,15…”
Section: Introductionmentioning
confidence: 99%